PERFORMANCE OF PUBLIC SERVICES OF THE POPULATION AND CIVIL RECORD SERVICES DURING PANDEMIC - Anis Septiana; Pitojo Budiono (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2022)
Performance is very important for organizations, especially government organizations. By measuring the performance of an organization, an organization can utilize and improve the effectiveness and efficiency of its human resources, as a basis for distributing awards, assisting in consideration and decision making efforts and identifying training needs and employee resource development. In connection with the existence of the Department of Population and Civil Registry of Bandar Lampung City, one of its main tasks is to make and issue identity cards and to handle personnel resource problems in order to improve the quality of apparatus resources properly and sustainably to support the implementation of the main tasks and functions as well as the achievement of Population work results. and Civil Registry of Bandar Lampung City. In an effort to achieve the work performance of Population and Civil Registry employees of Bandar Lampung City, it includes work motivation, ability, work environment, work discipline, leadership and personality. Based on the data on the website of the population and civil registration office of the city of Bandar Lampung, there are 7244 queues of recording electric ID cards that have not been processed and there are delays in the ID card making process which should have been completed on the specified schedule but has not been completed.